Statistical inference of exogenous and endogenous information propagation in social networks : doctoral thesis - Piškorec, Matija (M. Piškorec; Fakultet elektrotehnike i računarstva, 2019)
In the last decade we witnessed a rapid rise of the online social media services. Although they were created in the early 2000's, their rise began in earnest after 2010 when their presence started to fundamentally alter the traditional media landscape. Today, their influence on the way our society consumes, curates and disseminates information is indisputable. With their wider adoption came also the first criticism, as well as a need to solve emerging legislative, ethical and societal issues. One line of research is to explain and quantify the sources of influence in online social services and investigate to what extent are these new social landscapes vulnerable to manipulation by third parties. This manipulation is often performed by using user's digital traces - a record of their activities on the online social service. These digital footprints have a potential to characterize users in more detail than what they themselves would be willing to share otherwise. For example, user's personality traits can be inferred indirectly from the content with which they interact through online services, and even their writing style on the written content they published could be used to infer their demographic characteristics. This opens opportunities for micro-targeting of users for various dubious purposes, for example by increasing their propensity to spread misinformation.